2014
DOI: 10.1007/s12028-014-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis May Be an Option in Urgent Management of Heparin-Induced Thrombocytopenia in the Setting of Acute Intracerebral Hemorrhage

Abstract: This case helps illustrate the utility of plasmapheresis in management of HIT when anticoagulation is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Because this finding is consistent with reports in the literature, it is not surprising that for the CS indication, TPE treatment parameters such as plasma volume processed, number of procedures performed, and timing of the procedure prior to surgery were more clearly defined than for acute HIT with thrombosis. Nevertheless, there is still some variation in the number of TPE procedures needed for effective antibody reduction . Our survey findings appear to demonstrate equipoise between the number of CS patients that are treated with a set number of TPE procedures vs those treated to laboratory or clinical response.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Because this finding is consistent with reports in the literature, it is not surprising that for the CS indication, TPE treatment parameters such as plasma volume processed, number of procedures performed, and timing of the procedure prior to surgery were more clearly defined than for acute HIT with thrombosis. Nevertheless, there is still some variation in the number of TPE procedures needed for effective antibody reduction . Our survey findings appear to demonstrate equipoise between the number of CS patients that are treated with a set number of TPE procedures vs those treated to laboratory or clinical response.…”
Section: Discussionmentioning
confidence: 62%
“…However, once HIT is diagnosed, the primary course of action is to stop the offending anticoagulant and transition the patient to a parenteral DTI . As DTIs are primarily used in the management of HIT, TPE only becomes relevant in selected circumstances such as when continued anticoagulation is contraindicated; there is ongoing clinical deterioration despite DTI therapy; or there is need for heparin re‐exposure in the setting of CS …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one case, HIT antibodies decreased and HIPA became negative. 56 In the second case, HIPA was negative. 57 Post treatment heparin re-exposure Post-treatment heparin re-exposure occurred in two IVIGtreated cases.…”
Section: Changes In Hit Lab Parametersmentioning
confidence: 87%
“…Fourteen studies detailed the use of IVIG or TPE as initial therapy (see Table 2). Twelve studies included 13 case reports 46,[48][49][50][51][52][53][54][55][56][57][58] and one case series included four patients. 14 One case-controlled study of 44 patients reported aggregate data on 26 TPE-treated patients and is summarized separately.…”
Section: Treatment Indication 2: Initial Therapymentioning
confidence: 99%